Non-Performing Finance in Sharia Financial Institutions in Indonesia: A Case Study of BPRS Adeco (Aceh Development Corporation) - Hidayah, Nur; Tabrani, Tabrani (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2019)
High level of Non-Performing Finance (NPF) has become one of the risks faced by intermediary financial institutions, including Islamic banks. Indonesia’s Financial Authority found that NPF ratio of Islamic banks is relatively higher (4,12%) that one of the conventional banks (OJK, 2017). Literature indicates the influence of the bank’s internal and external factors on high NPF. This study aims to analyze the factors that influence the high level of NPF and its settlement and strategies to reduce the level of NPF in Sharia Rural Banking (BPRS/Bank Perkreditan Rakyat Syariah). Taking BPRS Adeco (Aceh Development Corporate) located in Langsa City District, Aceh, as a case study, this research takes a qualitative approach. Through a survey to 26 BPRS Adeco employees and semi-structured interviews with four employees, this study found three factors leading to an increase in the NPF ratio, namely weak bank’s financing risk management, changing economic conditions and regulations, and the conditions of customers who are vulnerable to socio-economic change. Tingkat Non-Performing Finance (NPF) yang tinggi telah menjadi salah satu risiko yang dihadapi oleh lembaga keuangan perantara, termasuk bank syariah. Otoritas Keuangan Indonesia menemukan bahwa rasio NPF bank syariah relatif lebih tinggi (4,12%) dibandingkan bank konvensional (OJK, 2017). Studi terdahulu menunjukkan pengaruh faktor internal dan eksternal bank terhadap NPF tinggi. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi tingginya level NPF dan solusinya, serta strategi untuk mengurangi tingkat NPF di Bank Perkreditan Rakyat Syariah (BPRS / Bank Kredensial Syariah). Penelitian ini menjadikan BPRS Adeco (Perusahaan Pembangunan Aceh) yang berlokasi di Kabupaten Kota Langsa, Aceh sebagai kasus, dengan menggunakan kualitatif. Melalui survei terhadap 26 BPRS Karyawan Adeco dan wawancara semi-terstruktur dengan empat karyawan, penelitian ini menemukan tiga faktor yang menyebabkan peningkatan rasio NPF, yaitu lemahnya manajemen resiko bank, perubahan kondisi dan regulasi ekonomi, dan kondisi konsumen yang rentan terhadap perubahan sosial ekonomi.